The 5-lipoxygenase pathway: oxidative and inflammatory contributions to the Alzheimer’s disease phenotype - Joshi, Yash B.; Praticò, Domenico (Frontiers in Cellular Neuroscience, 2015)
Alzheimer’s disease (AD) is the most common, and, arguably, one of the most-well studied, neurodegenerative conditions. Several decades of investigation have revealed that amyloid-β and tau proteins are critical pathological players in this condition. Genetic analyses have revealed specific mutations in the cellular machinery that produces amyloid-β, but these mutations are found in only a small fraction of patients with the early-onset variant of AD. In addition to development of amyloid-β and tau pathology, oxidative damage and inflammation are consistently found in the brains of these patients. The 5-lipoxygenase protein enzyme (5LO) and its downstream leukotriene metabolites have long been known to be important modulators of oxidation and inflammation in other disease states. Recent in vivo evidence using murine knock-out models has implicated the 5LO pathway, which also requires the 5LO activating protein (FLAP), in the molecular pathology of AD, including the metabolism of amyloid-β and tau. In this manuscript, we will provide an overview of 5LO and FLAP, discussing their involvement in biochemical pathways relevant to AD pathogenesis. We will also discuss how the 5LO pathway contributes to the molecular and behavioral insults seen in AD and provide an assessment of how targeting these proteins could lead to therapeutics relevant not only for Alzheimer’s disease, but also other related neurodegenerative conditions.